Improving leaping ability in elite rhythmic gymnasts - Hutchinson, M. R.; Tremain, L.; Christiansen, J.; Beitzel, J. (Medicine & Science in Sports & Exercise, 1998)
Elite rhythmic gymnasts can safely improve their leaping ability significantly through an intense course of jump training. Continued training with the leaping protocol does not appear to further enhance the benefit; however, the gains appear to be maintained at 4 months and 1 yr post training with or without additional training with the leaping protocol.